Non-phytate phosphorus equivalence for a novel E. coli phytase in corn and soybean meal diet fed to broiler chickens - Xuerong Song; Veronica Cheng; Li Xu; Faith Gituanjah; Chelsea Kibathi; Bianca Garcia; Felix Njeri; Reza Bakhshalinejad; Xiuyi Wu; Elijah G. Kiarie (Poultry Science)
A total of 2,060 d old male Ross x Ross 708 chicks were placed (22 birds/pen; Exp. 1) and (5 birds/cage, Exp. 2) to determine non-phytate phosphorous equivalence (NPPE) for a novel E. coli phytase in corn and soybean meal-based diets. Broiler chickens were fed common starter and transitioned to experimental diets for grower (d 8-21) and finisher (d 22-35) phases. Diets were formulated to meet specifications except for available P (AvP) that was reduced by 0.05 percent unit by adjusting monocalcium phosphorous (MCP) to create five titration diets. Phytase was supplemented in the diet with the lowest AvP at 250, 500, 1,000, 1,500 and 2,000 FTU/kg to create 10 test diets per phase. Diets were allocated to 8 (Exp. 1) and 6 (Exp. 2) replicates. Feed intake (FI), body weight (BW), BW gain (BWG), FCR, and bone attributes (breaking strength, BS, and ash content) were evaluated in Exp. 1, and apparent retention (AR) of Ca and P in Exp. 2. The BWG, FCR, and bone trait data were fitted in regression functions to estimate NPPE. Overall, increasing AvP linearly improved (P < 0.01) d 35 BW, BWG, FI, FCR, and BS. Overall (d 8-35) BWG, tibia and femur ash content increased linearly and FCR linearly and cubically in response to phytase (P < 0.05). The average NPPE values for the BWG and FCR during the grower phase were 0.060, 0.139, 0.175, 0.193, and 0.232 % at 250, 500, 1000, 1500, and 2000 FTU/kg, respectively. The corresponding values for the finisher phase were 0.122, 0.220, 0.316, 0.364, and 0.470 %, respectively. The average NPPE values for tibia and femur attributes were 0.075, 0.128, 0.180, 0.193 and 0.206 %, respectively for 250, 500, 1000, and 2000 FTU/kg. In conclusion, the study demonstrated the efficacy of the phytase in releasing phytate-bound P in corn and soybean meal diets, resulting in commensurate or superior growth and bone traits to diets enriched with inorganic P. The NPPE values will be valuable in formulating broiler chicken feeds.